The Role of Omega-3 in Attenuating Cardiac Remodeling and Heart Failure through the Oxidative Stress and Inflammation Pathways - Taline Lazzarin; Danilo Martins; Raquel S. Ballarin; Marina G. Monte; Marcos F. Minicucci; Bertha F. Polegato; Leonardo Zornoff (MDPI AG, 2023)
Cardiac remodeling is defined as molecular, cellular, and interstitial changes that manifest clinically as alterations in the size, shape, and function of the heart. Despite the pharmacological approaches, cardiac remodeling-related mortality rates remain high. Therefore, other therapeutic options are being increasingly studied. This review highlights the role of omega-3 as an adjunctive therapy to attenuate cardiac remodeling, with an emphasis on its antioxidant and anti-inflammatory actions.